Предмет: Алгебра, автор: milkovich12345

 lim_{x to  2} ( frac{1}{x-2} -  frac{12}{ x^{3}-8 } )

Ответы

Автор ответа: Аноним
0
 lim_{x to 2} ( frac{1}{x-2}- frac{12}{x^3-8}  )= lim_{x to 2}  (frac{1}{x-2} - frac{12}{(x-2)(x^2+2x+4)} )=\ \ \ = lim_{x to 2}  frac{x^2+2x+4-12}{(x-2)(x^2+2x+4)} = lim_{x to 2}  frac{x^2+2x-8}{(x-2)(x^2+2x+4)} = \ \ \ =lim_{x to 2}  frac{(x+4)(x-2)}{(x-2)(x^2+2x+4)} = lim_{x to 2}  frac{x+4}{x^2+2x+4} = frac{2+4}{2^2+2*2+4} = frac{1}{2}
Автор ответа: oganesbagoyan
0
OK !
Похожие вопросы
Предмет: Другие предметы, автор: Аноним